The Alignment between Institutions and Technology in Network Industries. Issue 2 (June 2013) - Crettenand, Nicolas; Finger, Matthias
Network industries, such as electricity, railways and air transport, are very complex technical, economic, and political systems in which the alignment between technology and institutions has a significant impact on performance. This alignment has been studied based on the coherence framework which aims to measure the alignment between technology and institutions in the case of network industries. It can be stated that technology has to be supported by institutions aligned with them (and vice versa) in order to deliver a given performance. This leads to a co-evolution between institutions and technology in network industries. This paper reviews the literature on the coherence framework, identifies its weaknesses, and contributes to the further development of the framework. It concludes with challenges for further research.